An Electronic Delphi Study to Establish Pediatric Intensive Care Nursing Research Priorities in Twenty European Countries - Tume, L.; van den Hoogen, A.; Wielenga, J.; Latour, Jos (Lippincott Williams & Wilkins, 2014)
Objectives: To identify and to establish research priorities for pediatric intensive care nursing science across Europe. Design: A modified three-round electronic Delphi technique was applied. Questionnaires were translated into seven different languages. Setting: European PICUs. Participants: The participants included pediatric intensive care clinical nurses, managers, educators, and researchers. In round 1, the qualitative responses were analyzed by content analysis and a list of research statements and domains was generated. In rounds 2 and 3, the statements were ranked on a scale of one to six (not important to most important). Mean scores and SDs were calculated for rounds 2 and 3. Interventions: None. Measurements and Main Results: Round 1 started with 90 participants, with round 3 completed by 64 (71%). The seven highest ranking statements (≥ 5.0 mean score) were related to end-of-life care, decision making around forgoing and sustaining treatment, prevention of pain, education and competencies for pediatric intensive care nurses, reducing healthcare-associated infections, identifying appropriate nurse staffing levels, and implementing evidence into nursing practice. Nine research domains were prioritized, and these were as follows: 1) clinical nursing care practices, 2) pain and sedation, 3) quality and safety, 4) respiratory and mechanical ventilation, 5) child- and family-centered care, 6) ethics, 7) professional issues in nursing, 8) hemodynamcis and resuscitation, and 9) trauma and neurocritical care. Conclusions: The results of this study inform the European Society of Pediatric and Neonatal Intensive Care’s nursing research agenda in the future. The results allow nurse researchers within Europe to encourage collaborative initiatives for nursing research.